(untitled) (Bangladesh Journal of Zoology, 2023)
Malaria, caused by the Plasmodium parasite, contributes to a significant global health burden that disproportionally affects those living in developing nations. The majority of cases are caused by the species P. falciparum and responsible for the a million deaths each year worldwide. The aim of the present study was to evaluate extracts of three indigenous medicinal plants- Raishorisha, Brassica juncea; Gimma shak, Glinus oppositifolius and Hijal, Barringtonia acutangula In vitro anti-plasmodial activities against the 3D7 laboratory strain of Plasmodium falciparum, which is sensitive to all drug was tested. HRP2 ELISA assay was used to evaluate the in vitro inhibitory activity of the extracts. Plant extracts showed moderate to good anti parasitic effects. Highly promising anti-plasmodial activity was found in the extract of Brassica juncea. 50% inhibitory concentration (IC50) 3D7: 0.00905 μg/ml (methanol extract), and Glinus oppositifolius had a good activity (IC50) 3D7: 13.8 μg/ml (methanol extract). A moderate activity (23.8 μg/ml) was found in the methanol extracts of B. acutangula. These results demonstrate that methanol extracts of B. juncea and G. oppositifolius may have antimalarial agents even in their crude form. The isolation of compounds from these two plants seems to be of special interest for further anti-malarial studies. Bangladesh J. Zool. 51(2): 205-216, 2023